Numerical analysis of the electromagnetic force for design optimization of a rectangular direct current electromagnetic pump - Lee, Geun Hyeong; Kim, Hee Reyoung (Nuclear engineering and technology, 2018)
The force of a direct current (DC) electromagnetic pump used to transport liquid lithium was analyzed to optimize its geometrical and electrical parameters by numerical simulation. In a heavy-ion accelerator, which is being developed in Korea, a liquid lithium film is utilized for its high charge-stripping efficiency for heavy ions of uranium. A DC electromagnetic pump with a flow rate of 6 cm3/s and a developed pressure of 1.5 MPa at a temperature of 200°C was required to circulate the liquid lithium to form liquid lithium films. The current and magnetic flux densities in the flow gap, where a Sm2Co17 permanent magnet was used to generate a magnetic field, were analyzed for the electromagnetic force distribution generated in the pump. The pressure developed by the Lorentz force on the electromagnetic force was calculated by considering the electromotive force and hydraulic pressure drop in the narrow flow channel. The opposite force at the end part due to the magnetic flux density in the opposite direction depended on the pump geometrical parameters such as the pump duct length and width that defines the rectangular channels in the nonhomogeneous distributions of the current and magnetic fields.